2013
DOI: 10.1088/0004-637x/779/2/127
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Light From Young Cosmic Cities: Physical and Observational Signatures of Galaxy Proto-Clusters

Abstract: A growing number of galaxy clusters at z =1-2 is being discovered as part of deep optical, IR, X-ray, and Sunyaev-Zel'dovich effect surveys. For a complete picture of cluster formation, however, it is important that we also start probing the much earlier epoch, between redshifts of about 2 and 7, during which these clusters and their galaxies first began to form. Because the study of these so-called "proto-clusters" is currently quite limited by small number statistics, widely varying selection techniques, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
539
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(598 citation statements)
references
References 121 publications
42
539
2
1
Order By: Relevance
“…Since the TNJ1338 field has higher G than the whole simulation (and the SXDS field), the number density of TNJ1338-like field is thought to be close to that of such high-G fields. The number density is thus comparable to that of Coma-type protoclusters identified in the same simulation (58 protoclusters; Chiang et al 2013). The number (21 peaks) corresponds to number density of 6.4 × 10 −8 Mpc −3 in comoving units.…”
Section: Density Field Of the Whole Simulated Mapsupporting
confidence: 65%
See 2 more Smart Citations
“…Since the TNJ1338 field has higher G than the whole simulation (and the SXDS field), the number density of TNJ1338-like field is thought to be close to that of such high-G fields. The number density is thus comparable to that of Coma-type protoclusters identified in the same simulation (58 protoclusters; Chiang et al 2013). The number (21 peaks) corresponds to number density of 6.4 × 10 −8 Mpc −3 in comoving units.…”
Section: Density Field Of the Whole Simulated Mapsupporting
confidence: 65%
“…a protocluster (Venemans et al 2002(Venemans et al , 2007Miley et al 2004;Intema et al 2006;Overzier et al 2008). Theoretical simulations also suggests that the overdensity associated with TNJ1338 is likely to be an ancestor of a present-day cluster (Chiang, Overzier & Gebhardt 2013). Multiwavelength observations have shown that this source has radio lobes with an extent of ∼70 kpc.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Beyond z ∼ 2.5 there are few massive groups within protoclusters (Chiang, Overzier & Gebhardt 2013), so we expect the environmental effects we observe at z = 1.6 to decrease at higher redshifts. The passive fraction of protoclusters at z > 2 is difficult to measure, but there is some evidence that suggests that the suppression of star formation within protoclusters decreases at z > 2 (Cooke et al 2014;Husband et al 2016;Wang et al 2016).…”
Section: The Evolution Of Environmental Effects In Protoclustersmentioning
confidence: 81%
“…Recently progress towards this has been made by Chiang, Overzier & Gebhardt (2013) who demonstrate there is a strong correlation between the descendant z = 0 cluster mass and the mass overdensity of a protocluster over large volumes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) diameter). The uncertainty of the descendant z = 0 cluster mass for each protocluster is very large, due to both intrinsic scatter in the relation and the inherent problems in converting the observed projected galaxy overdensity into the true 3D mass overdensity (Shattow et al 2013), but such methods can be successful in estimating the statistically likely mass of a large sample of protoclusters.…”
Section: Introductionmentioning
confidence: 99%